Calcium Carbonate Dissolution Triggered by High Productivity During the Last Glacial–Interglacial Interval in the Deep Western South Atlantic - Suárez-Ibarra, Jaime Y.; Frozza, Cristiane F.; Palhano, Pâmela L.; Petró, Sandro M.; Weinkauf, Manuel F. G.; Pivel, Maria A. G. (Frontiers in Earth Science, 2022)
Studies reconstructing surface paleoproductivity and benthic environmental conditions allow us to measure the effectiveness of the biological pump, an important mechanism in the global climate system. In order to assess surface productivity changes and their effect on the seafloor, we studied the sediment core SAT-048A, spanning 43–5 ka, recovered from the continental slope (1542 m water depth) of the southernmost Brazilian continental margin, deep western South Atlantic. We assessed the sea surface productivity, the organic matter flux to the seafloor, and calcite dissolution effects, based on micropaleontological (benthic and planktonic foraminifers, ostracods), geochemical (benthic δ13C isotopes), and sedimentological data (carbonate and bulk sand content). Superimposed on the induced changes related to the last glacial–interglacial transition, the reconstruction indicates a significant and positive correlation between the paleoproductivity proxies and the summer insolation. From the reconstructed data, it was possible to identify high (low) surface productivity, high (low) organic matter flux to the seafloor, and high (low) dissolution rates of planktonic Foraminifera tests during the glacial (postglacial). Furthermore, within the glacial, enhanced productivity was associated with higher insolation values, explained by increased NE summer winds that promoted meandering and upwelling of the nutrient-rich South Atlantic Central Water. Statistical analyses support the idea that productivity is the main cause for seafloor calcium carbonate dissolution, as opposed to changes in the Atlantic Meridional Overturning Circulation (at least for the 25–4 ka period). Further efforts must be invested in the comprehension and quantification of the total organic matter and biogenic carbonate burial during time intervals with an enhanced biological pump, aiming to better understand their individual roles.